Mitonuclear genomics and aging - Reynolds, Joseph C.; Bwiza, Conscience P.; Lee, Changhan (Human Genetics, 2020)
Our cells operate based on two distinct genomes that are enclosed in the nucleus and mitochondria. The mitochondrial genome presumably originates from endosymbiotic bacteria. With time, a large portion of the original genes in the bacterial genome is considered to have been lost or transferred to the nuclear genome, leaving a reduced 16.5 Kb circular mitochondrial DNA (mtDNA). Traditionally only 37 genes, including 13 proteins, were thought to be encoded within mtDNA, its genetic repertoire is expanding with the identification of mitochondrial-derived peptides (MDPs). The biology of aging has been largely unveiled to be regulated by genes that are encoded in the nuclear genome, whereas the mitochondrial genome remained more cryptic. However, recent studies position mitochondria and mtDNA as an important counterpart to the nuclear genome, whereby the two organelles constantly regulate each other. Thus, the genomic network that regulates lifespan and/or healthspan is likely constituted by two unique, yet co-evolved, genomes. Here, we will discuss aspects of mitochondrial biology, especially mitochondrial communication that may add substantial momentum to aging research by accounting for both mitonuclear genomes to more comprehensively and inclusively map the genetic and molecular networks that govern aging and age-related diseases.